2017
DOI: 10.1007/978-1-4939-6892-3_17
|View full text |Cite
|
Sign up to set email alerts
|

Human Telomeric G-Quadruplex Structures and G-Quadruplex-Interactive Compounds

Abstract: G-quadruplexes are noncanonical secondary structures formed in DNA sequences containing consecutive runs of guanines. It has been shown that the 3′ G-rich single-stranded overhangs of human telomeres can form G-quadruplex structures, and the human telomeric DNA G-quadruplexes are considered attractive targets for anticancer drugs. G-quadruplex-interactive compounds have been shown to inhibit telomerase access as well as telomere capping. Nuclear magnetic resonance (NMR) spectroscopy is a powerful method in det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 57 publications
1
28
0
Order By: Relevance
“…Thew tTel23 sequence is known to form awell characterized G-quadruplex in presence of K + ions. [35] Thew tTel23 G-quadruplex was folded in the presence of 100 mm KCl and we confirmed that the wtTel23 oligonucleotide used in this study adopted the previously reported hybrid-1 G-quadruplex topology by acomparison of 1 H-NMR spectra to published literature ( Figure S11). [35] After the addition of the folded wtTel23 to the copper chelated polymer nanodiscs the non-overlapped NMR fingerprint showed no significant change in the 1 H-NMR spectrum indicating the retention of hybrid-1 G-quadruplex topology ( Figure S12).…”
supporting
confidence: 88%
“…Thew tTel23 sequence is known to form awell characterized G-quadruplex in presence of K + ions. [35] Thew tTel23 G-quadruplex was folded in the presence of 100 mm KCl and we confirmed that the wtTel23 oligonucleotide used in this study adopted the previously reported hybrid-1 G-quadruplex topology by acomparison of 1 H-NMR spectra to published literature ( Figure S11). [35] After the addition of the folded wtTel23 to the copper chelated polymer nanodiscs the non-overlapped NMR fingerprint showed no significant change in the 1 H-NMR spectrum indicating the retention of hybrid-1 G-quadruplex topology ( Figure S12).…”
supporting
confidence: 88%
“…G4 in telomeres acts as tumor suppressor by inhibiting telomerase thereby maintaining the telomere [16][17][18] . Telomeric quadruplexes are highly conserved and are associated with numerous telomeric proteins 19 .…”
mentioning
confidence: 99%
“…This means that the structure can be formed from a range of one to four different guanine rich DNA strands. [3][4] The main structure of a G-Quadruplex is, however, consistent regardless of the number of strands involved in its formation. A G-Quadruplex structure consists of multiple layers of planes, usually between two to four layers, stacked on top of each other in a parallel fashion.…”
Section: G-quadruplexmentioning
confidence: 96%
“…The human telomeric G-Quadruplex also happened to be the first biologically applicable G-Quadruplex formation to be identified. [3][4] Human telomere refers to the overhang found at the tail end of each human chromosome which consists of usually 100-200 repeated nucleotide sequences, known as TTAGGG repeats, that are guanine rich. 4 The main purpose of the telomeres is to safeguard the integrity of the chromosomes by preventing them from self-decaying or binding to neighboring chromosomes.…”
Section: Human Telomeric G-quadruplexmentioning
confidence: 99%